Pengaruh Pemberian Abu Cangkang Kerang Laut dan Pupuk SP-36 Terhadap Pertumbuhan dan Hasil Tanaman Tomat Pada Tanah Gambut - Normalita Puteri, Afira Afra; Supriyanto, Supriyanto; Aprizkiyandari, Siti (Fakultas Pertanian Universitas Tanjungpura, 2025)
The development of tomato plants on peat soils has problems including low soil pH and low nutrient availability. Efforts to overcome these problems require liming which aims to increase the pH of peat soil. The ameliorant material used is Sea Shell Ash to improve the biological, physical, and chemical properties of the soil, and the addition of SP-36 fertilizer to increase the growth and yield of tomato plants. This study aims to obtain the best dose of sea shell ash and SP-36 fertilizer for the growth and yield of tomato plants on peat soil. The research was conducted at Bengkayang Dormitory, Jalan Sepakat, from June to August. The design used was a complete randomized design (CRD) consisting of 2 factors, namely the Shell Ash factor (A) and SP-36 Fertilizer (P). The seashell ash factor is a1: with 100 g/polybag, a2: with 200 g/polybag, and a3; with 300 g/polybag. The SP-36 fertilizer factor is p1: with 2 g/polybag SP-36 fertilizer, p2: with 4 g/polybag SP-36 fertilizer, and p3: with 5 g/polybag SP-36 fertilizer. The observation variables in this study included: plant height (cm), root volume (cm3), plant dry weight (g), number of fruits per plant (fruit), fruit weight per plant (g), and weight per fruit (g). The results showed that SP-36 fertilizer had no effect on the yield of tomato plants, but cane ash did.